Incarceration and structural racism in Latin America and Brazil - França, Rosilene Marques Sobrinho de (Argumentum, 2022)
The work analyzes the process of implementation of prisons and the role played by prison in the Brazilian and Latin American historical trajectory, with reflections on structural racism and its consequences for the poor, black and peripheral population. The methodology consisted of a bibliographical and documental study. The results showed that there is a paradox and also an incisive articulation between incarceration, structural racism and the resurgence of criminal legislation and criminal procedure in Latin America and Brazil, since at the time when a list of rights were formally conquered, from the redemocratization processes, penal selectivity, punitivism and the war on drugs presented a perspective of mass incarceration, as a form of social control of the poor, black population living in urban peripheries today.